Analisis Semiotika Charles Sanders Pierce pada Karikatur Cover Majalah Tempo Edisi 16-22 September 2019 - Naida Rahma Tania; R. Myrna Nur Sakinah; Dadan Rusmana (LPPM Universitas Terbuka, 2022)
This research aims to identify the representamen or sign, object, and interpretant on Tempo magazine cover of the 16-22 September 2019 edition. Tempo magazine carries political elements, and it is interesting to analyze. The caricature of the Indonesian President is used as the primary discussion to seek the messages that are being delivered. The magazine cover conveys meanings. This study uses qualitative research by using Charles Sanders Peirce's semiotic analysis. The study focuses on signs which are divided into three categories: representamen, object, and interpretant. The finding shows that the caricature implies that the President of Indonesia betrayed himself and the citizens. His promise to make the Corruption Eradication Commission (KPK) stronger was only an empty promise. The controversial icon of Pinocchio is associated with the Indonesian president because of the revision of Law No. 30 2002 that weakens KPK.